Afetividade de adolescentes praticantes de atividades esportivas com relação ao seu bairro - Souza, Ricardo Angelo de Andrade (2009)
Sport and/or sportive activities as a whole should be accepted not only as a possibility of improving socio-economic conditions but also as instruments that trigger ever-increasing affects within individual-object relationship. Affective map (BOMFIM 2003) was the instrument this study used to analyze how affects arise in individual-sport-environment relationship. The research used a survey of nineteen 12-to-17 years-old teenagers who practice sportive activities and attend to a NGO (non governmental organization) named ARCA (Associação Recreativa e Esportiva para Crianças e Adolescentes). Therefore the sense of this study was verifying how sport arises at the neighborhood through Affective map gathering information from teenagers who practice systematic sportive activities. The work focused sportive experience related to the neighborhood from affective axe. Thus such concept was theoretically based on Lane and Sawaia (1994) Sawaia (2000, 2004) and also on Sport psychology (SAMULSKI 2002 WEINBERG & GOULD 2001). As results the research found that the most part of teenagers suggested both in qualitatively part and in Likert scale of affective maps contrasts images pleasure pertinence and destruction. In both analyses the contrasts image showed the highest mean according to descriptive statistics. Findings are evidence that sport even quoted in constrasting images is entailed to positive esteem since qualitative analysis of affective maps points that such practices arise as counterparts of negative aspects concerning to the neighborhood as violence drugs and pollution. Besides frequencies obtained with Likert scale of pleasure and pertinence suggest that sportive practice can generate other positive affects related to the neighborhood. Hence the study stresses that sport as a whole can lead teens not only to the highest place of a podium but also to an improvement in the relationship with their place of living aiding to establish new possibilities within the new horizon opened around them. Still psychology specifically Environmental Psychology can also help in this way this challenge this new environment that sport represents